Damping based on electromagnetic induction: A comparison of different minimal models. Issue 1 (25th January 2021) - Rosenboom, Mitja; Hetzler, Hartmut
Abstract: Damping of structural vibrations is a crucial part of modern engineering. Using electromagnetic interactions for this purpose is a modern and promising approach. To gain better understanding of phenomena involved in this technique investigations on minimal models of a B‐field modulation dampers are shown. Therefore two different setups are compared. One uses a permanent magnet as the source for the magnetic field, one uses a coil, respectively an electro‐magnet as the source. The contribution focuses on differences that occur, due to the different designs. Therefore the static behavior is analyzed as well as the system response on a harmonic force excitation.